Factors influencing the sustainable energy technologies adaptation in ASEAN countries. (October 2022) - Lin, Chia-Yang; Chau, Ka Yin; Moslehpour, Massoud; Linh, Hoang Viet; Duong, Khoa Dang; Ngo, Thanh Quang
Abstract: Sustainable energy technology adoption has become a global requirement due to environmental degradation, and this phenomenon needs researchers' and regulators' emphasis. Hence, the present study examines the various factors such as low cost, awareness of the environment, attribution of responsibility, habitual energy-saving behavior, and social norms impact on the sustainable energy technologies adoption in ASEAN countries. The article has taken the questionnaires to collect the data from the chosen respondents. The research has also applied structural equation models (SEM) using SPSS-AMOS to test the hypotheses and association among the variables. The results indicated that the low cost, awareness of the environment, attribution of responsibility, and habitual energy-saving behavior are positively correlated with sustainable energy technologies adoption in a sample of ASEAN economies. The findings also exposed that the social norms and sustainable energy technologies adoption are negatively correlated in chosen sample. This study guides the regulators in establishing the policies related to sustainable energy technologies adoption by examining the features mentioned in the study.